Kinetics of Reduction of Iron Ore Powder by Industrial Lignin from Pulping and Papermaking Waste Biomass Energy - Wendi Zhou; Dongwen Xiang; Qiang Zhang; Guoqing Wu; Yajie Wang; Dong Li; Qinghua Zhang; Huaxin Hu (Crystals)
To explore the application of industrial lignin, a waste biomass resource, in the field of metallurgy, the kinetic behavior of iron ore powder reduction by Shenmu bituminous coal, Lu’an anthracite, and industrial lignin under different carbon–oxygen molar ratios (nc:no = 0.5, 0.7, 1.0, 1.2, and 1.5) was studied using a thermogravimetric analyzer and reduction furnace. The results show that the reduction process of iron ore powder with three reducing agents conforms to the D1 model, that is, the kinetic equation is <semantics>G(α)=α2</semantics>. Under the same carbon–oxygen molar ratio, the activation energy of the iron ore powder reduced by industrial lignin is lower than that of pulverized coal. The activation energy increases first, then decreases and then increases with the increase in the carbon–oxygen molar ratio. When the molar ratio of carbon to oxygen is 1.2, the reaction activation energy is the lowest. At this time, the reaction activation energy of industrial lignin reduction iron ore powder is 14.21 kJ·mol−1, that of Shenmu bituminous coal is 16.81 kJ·mol−1, and that of Lu’an anthracite is 37.13 kJ·mol−1.